La educación rural y sus desafíos en el siglo XXI - Sandra Ovares-Barquero; Nuria Méndez-Garita; Nancy Torres-Victoria; Yadira Cerdas-Rivera (Universidad Nacional, Costa Rica, 2007)
This article is about the challenges of rural education in the XXI century. It describes the process experienced by rural populations in Costa Rica and the exclusion suffered by indigenous and inmigrants. At the end, the author offers different proposals that could be incorporated not only in educational curricula but also as a guide for professionals who work in these regions.